A proposal of an analytical conflict management model for the Chinese context - Falcão, P. F.; Faria, R. de O.; Costa, R. L. da. (Proceedings of the International Conference of Applied Business and Management (ICABM2020), 2020)
China’s culture is different from Western cultures, with various implications including conflict management styles. Many conflict management studies have been based in a set of models with the same or similar assumptions, namely two axis related with concern for self and concern for the other or for the relationship with the other, that produce four or five conflict management styles (e.g., Rahim 2002). However, those similar models do not reflect China’s culture. This study aims to create a model for conflict management styles structure definition that is adapted to Chinese culture.